Charm and beauty production in hadronic collisions via muon measurements at forward rapidity with ALICE - Zhang Maolin (EPJ Web of Conferences)
The latest results from the ALICE Collaboration on the measurements of open heavy flavours in the (di)muon channel at forward rapidity are presented. In the LHC Run 3, the new Muon Forward Tracker (MFT) adds vertex capabilities to the muon spectrometer, providing a unique way to discriminate muons from charm- and beauty-hadron decays. The analysis strategy is discussed and the status of the measurements in pp collisions at √s = 13.6 TeV collected with the upgraded ALICE detector is reported.